Prenucleation clusters and non-classical nucleation - Gebauer, Denis; Cölfen, H. (Elsevier, 2011)
In this contribution, we review the recent literature on an alternative crystallization pathway involving stable clusters prior to nucleation and show that the prenucleation cluster pathway is a truly non-classical concept of nucleation. Prenucleation clusters are solutes with "molecular" character in aqueous solution. It becomes evident that the stable clusters may have been concealed by the so-called ion pair concept and activity effects. We show that non-classical nucleation via stable prenucleation clusters is a highly valuable concept for a novel understanding of phenomena observed in bio- and biomimetic mineralization, which however may hardly be rationalized by means of classical nucleation theory. The importance to combine experimental and theoretical studies is emphasized. © 2011 Elsevier Ltd.